What Protects Adolescents with Youth Subculture Affiliation from Excessive Internet Use? - Filakovska Bobakova, Daniela; Holubcikova, Jana; Madarasova Geckova, Andrea; Dankulincova Veselska, Zuzana (International journal of environmental research and public health, 2018)
Youth subculture affiliation (SA) appears to be an important risk factor with regard to adolescents' problem behavior. Excessive Internet use (EIU) has emerged as a new type of problem behavior; however, it has not yet been studied in adolescents affiliated with youth subcultures. Thus, the aim of this study was to assess the association between SA and EIU and to explore the role of selected protective factors. We used data from the Health Behaviour in School-aged Children (HBSC) study conducted in 2014 in Slovakia. The final sample for this study comprised 532 adolescents (mean age: 15.4; 49.6% boys). Hierarchical linear regression analysis was conducted to examine the associations of EIU with SA. Adolescents with SA were more likely to report EIU. Adjustment for protective factors decreased the association between EIU and SA. From all tested interactions, only the interaction of SA with family support was found to be significant. The relationship between family support and EIU was mediated via Monitoring by the mother only in adolescents without SA. Our findings imply that the risk of EIU is higher in adolescents with SA. There was a difference in how protective factors worked in adolescents with and without SA.
Keywords: Surveys and Questionnaires; návykové chování; Humans; ochranné faktory; chování mladistvých; Female; youth subcultures; Family Relations; Protective Factors; lidé; Slovakia; Slovenská republika; adolescence; excessive Internet use; průzkumy a dotazníky; internet; ženské pohlaví; Internet; sociální identifikace; Adolescent Behavior; Male; Adolescent; protective factors; Social Identification; rodinné vztahy; mužské pohlaví; Behavior, Addictive; mladiství